Voting Right as Legal and Ethical Category - Rajić, Nataša; Orlović, Slobodan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Voting right is a subjective public right and belongs to the group of a basic political rights. It could be considered as a legal as well as an ethical category. These two aspects are not completely separable and they are closely connected to a constitutional culture level of a concrete society. Thereof, a high percentage of electoral turnout could not be exclusively a consequence of compulsory voting as well as sanction which follow the violation of this obligation. A lower percentage of electoral turnout could also have a positive impact on dynamic of relationship between citizen – government, if it represents a constructive expression toward a political elite and its crucial decisions.